Catalytic thermal cracking of Athabasca VR in a closed reactor system. (1st April 2018) - Eshraghian, Afrooz; Husein, Maen M.
Graphical abstract: Highlights: Catalytic thermal cracking of Athabasca vacuum residue was studied in an autoclave. Higher liquid yield was obtained relative to the literature. Catalysts contributed to higher rate and better quality maltene. Optimum drill cuttings dose slowed down coke precursor polymerization. Thermogravimetry profiles were initial mass-dependent. Abstract: Catalytic thermal cracking of the residue is less common, due to high susceptibility of catalysts to deactivation. In this work, cracking of Athabasca vacuum residue in an autoclave at 400 °C was investigated in presence of in situ prepared and commercial alumina nanoparticles as well as drill cuttings. A high liquid yield of ∼90 wt% was obtained. The nanoparticles and drill cuttings (at 30 wt%) contributed to relatively high coke and gas yields. Nevertheless, the catalytic runs had higher quality maltene product. Reducing drill cuttings concentration to 10 wt% gave the highest liquid yield with high quality maltene. Coke inhibition in presence of optimum drill cuttings concentration is attributed to a balance between the rate of coke precursor formation and adsorption onto the cuttings. Subsequently, at a higher temperature, 420 °C, the higher rate of precursor formation led to similar results between the 10 wt% drill cuttings and the control sample. Both toluene insolubles and produced asphaltenes displayed a lower H/C ratio than asphaltenes in the feed, in line with the thermal cracking activity. Thermogravimetry profiles for the produced asphaltenes was attained at higher temperatures than the toluene insolubles, and was initial-mass sensitive. Accordingly, thermogravimetry profiles should not be indefinitely used to identify the different oil fractions.